DYNAMICS MODELING AND CONTROL SYSTEM DEFINITION FOR VIBRATION ATTENUATION OF A THIN TITANIUM PLATE WITH MATLAB AND ANSYS - Vlad Mihai PANAINTE; Horia BĂLAN (Carpathian Journal of Electrical Engineering, 2022)
Vibration artefacts that appear at small dimension components are frequently encountered in multiple domains such electronic equipment production, surgical and high precision medical applications, optical applications high quality photo/video equipment. The main objective of this work is to develop a reduced model that accurately represents the dynamics of a small dimension titanium plate and define a suitable vibration control system. With the aid of powerful engineering software instruments, the mathematical model of the studied object is defined with MATLAB after it was modeled and analyzed with ANSYS (mode shape analysis). The mathematical model is developed based on the eigenvectors and eigenvalues extracted from ANSYS and it is called the state space model which is than transformed into a transfer function for simplicity reasons. The mathematical model is than integrated in Simulink and the vibration velocity is evaluated, followed by the definition of a control system comprised of a piezoelectric actuator and PID controller. The evaluation of the system was performed by applying a step signal at the input of the plant and the velocity response is observed comparatively in three configurations as listed: small dimension plate response, plate and piezoelectric actuator and full plant (titanium plate, actuator and PID controller.